Penyuluhan Harmonisasi Keluarga Dalam Bentuk Ice Breaking: Tinjauan Filosofis Historis Pada Tepuk Sakinah - Mukminin, Ikhwanul; Ali, Muhammad Irza Tsaquf; Al Faruq, Abdul Qudus; Salsabilla, Selena Chayka (Universitas Cokroaminoto Yogyakarta, 2026)
This qualitative research discusses the teaching of family harmony through the ice breaking method in the form of Tepuk Sakinah as an educational medium within the Ministry of Religious Affairs with a philosophical and historical review. The method used is library research and documentation, with data sources coming from books, journals, official guidelines of the Ministry of Religious Affairs, and literature related to Islamic family education. The analysis was conducted by tracing the ontological, epistemological, and axiological aspects of the Tepuk Sakinah concept and its historical journey as a means of family development. Tepuk Sakinah is an effective method of da'wah and value education in conveying moral messages in a fun and contextual manner. Philosophically, the activity contains the values ​​of peace, compassion, and responsibility which historically reflect the Ministry of Religious Affairs' innovation in family education models that are relevant to society.